The Traditional Village Represented in Romania’s Open-Air Ethnographic Museums - Buzas, Andreea (Ethnographica et Folkloristica Carpathica, 2023)
This paper work is a very brief presentation that brings the reader into the front of the most important open-air museums from Romania and tries to emphasize the value of their identity. This work is, in fact, a presentation of an extensive doctoral program, after which we will publish a book, and we hope that we will be able to develop certain topics right in the pages of the journal Ethnographica et Folkloristica Carpathica. The quick development of museums has generated a veritable Romanian school of museography, recognized both nationally and internationally. The source of this development is represented by the speech of museum; that is how the museum manages to revaluate its available potential and to get imposed in areas of interest from most various: scientific, educational, cultural, touristic, ensuring the representation of as many ethnographical areas as possible. Although the concept of ethnographical museum allows multiple approaches and definitions, this essay highlights the role of the identity of museums and their way of representing the traditional village, given the dynamics and the abandonment of traditions.